Letter to House of Representatives - Stephens, Alexander (My University, 1879)
Letter from Alexander Stephens to House of Representatives, January 14, 1879.
Letter from Alexander Stephens to House of Representatives, January 14, 1879. Eugene Beck Collection. 1 handwritten letter. 1 page.
Keywords: Letters; Records and correspondence; United States. Congress. House; Stephens, Alexander H. (Alexander Hamilton), 1812-1883